2015
DOI: 10.3390/ijms160819419
|View full text |Cite
|
Sign up to set email alerts
|

Lentiviral-Mediated Short Hairpin RNA Knockdown of MTDHInhibits Cell Growth and Induces Apoptosis by Regulatingthe PTEN/AKT Pathway in Hepatocellular Carcinoma

Abstract: The activation of oncogenes and the loss of tumor suppressor genes are believed to play critical roles in the pathogenesis of human hepatocellular carcinoma (HCC). Metaherin (MTDH), also called astrocyte elevated gene-1 (AEG-1), is frequently amplified in a variety of cancers, but the roles of MTDH with regard to growth and apoptosis in HCC have not yet been studied. In the present study, we first analyzed the expression of MTDH in HCC samples. We found that MTDH protein levels are higher in most HCC cancerous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…With further studies, the expression of MTDH is associated with the development of cancers and the high expression is especially found in the aggressive metastatic stage (25). It was also identified that the overall survival rate and prognosis were poorer in HCC patients with MTDH overexpression (22). MTDH is overexpressed in 90% of HCC patients and plays a pivotal role in HCC (26), which suggests that MTDH may serve as an ideal target for anti-HCC therapy.…”
Section: Mir-217 Suppresses Proliferation Migration and Invasion Prmentioning
confidence: 99%
See 1 more Smart Citation
“…With further studies, the expression of MTDH is associated with the development of cancers and the high expression is especially found in the aggressive metastatic stage (25). It was also identified that the overall survival rate and prognosis were poorer in HCC patients with MTDH overexpression (22). MTDH is overexpressed in 90% of HCC patients and plays a pivotal role in HCC (26), which suggests that MTDH may serve as an ideal target for anti-HCC therapy.…”
Section: Mir-217 Suppresses Proliferation Migration and Invasion Prmentioning
confidence: 99%
“…Metadherin (MTDH), a 582-amino acid single pass transmembrane protein, is also known as lysine-rich CEACAM1 co-isolated (LYRIC) and astrocyte elevated gene-1 (AEG-1) (22). Since its initial cloning in 2002 (23), plenty of studies have demonstrated that MTDH expression is elevated in a great diversity of cancers (24), such as hepatocellular renal cell and gallbladder carcinomas, colorectal, gastric, prostate,…”
Section: Introductionmentioning
confidence: 99%
“…34 Recent studies have demonstrated that MTDH knockdown leads to the inhibition of cell growth and induces the apoptosis in human retinoblastoma as well as in hepatocellular carcinoma. 35, 36 Here we showed that Mtdh is expressed in the tubules as well as the glomeruli, predominantly in podocytes. Furthermore, Mtdh expression was shown to be increased in the renal tissues of db/db mice, in the glomeruli form streptozotocin-induced diabetic rats and in HG-induced MPC5, and that Mtdh inhibition leads to the reduction in HG-induced MPC5 apoptosis.…”
Section: Discussionmentioning
confidence: 73%
“…(Tian et al 2017) miR-217 partially inhibits hepatic metastasis by binding to the 3'-UTR of MTDH mRNA, (Su et al 2014;Zhang et al 2017) which encodes a protein that can induce cell growth and inhibit apoptosis. (Li et al 2015) However, miR-217 was also found to be overexpressed in HCC and is potentially involved in promoting hepatic disease. (Jiang et al 2017) miR-217 induces cancer stem cell-like phenotypes resulting in the activation of the Wnt pathway in HCC cells.…”
Section: Discussionmentioning
confidence: 99%